Innovation of student worksheet (lkpd) based on geblek renteng local wisdom for grade V elementary school students - Nova Riswanti; Annery Fienta; Ali Mustadi; Sammy Enggar Patalatu (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Integrating local wisdom into student worksheets (LKPD) helps learners connect with their surrounding culture, fostering a deeper sense of appreciation and pride in their regional heritage. This study aimed to develop student worksheets that integrate the local wisdom of Geblek Renteng into the economic concepts taught in the Indonesian language curriculum, using concrete examples from students' immediate surroundings. The participants in this research were 15 fifth-grade elementary school students. This study employed the ADDIE Research and Development (R&D) model, which encompasses five systematic phases: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. Data were collected through observations, interviews, needs analysis questionnaires, and validation surveys administered to media and subject matter experts, alongside feedback forms for teachers and students. The gathered data were subsequently evaluated using quantitative descriptive analysis techniques. Validation results from subject matter and media experts indicated that the product is "Highly Feasible," achieving average scores of 83% and 87%, respectively. Furthermore, responses from teachers and students classified the product as "Highly Practical," with average scores of 94% and 97%, respectively. Ultimately, it can be concluded that the newly developed worksheets based on the Geblek Renteng local wisdom are both feasible and practical for implementation in the learning process.